BUDAYA KOLABORATIF DI DINAS LINGKUNGAN HIDUP KABUPATEN REMBANG - Gelora Kasih, Johnsen Hezron; Hanani, Retna; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Collaboration is one of the eight elements in ASN's Core Values of AKHLAK. These ASN Core Values with AKHLAK are a summary of the main values of the State Civil Service in accordance with Law no. 5 of 2014 concerning State Civil Apparatus. The Rembang Regency Environmental Service is one of the regional organizations that has various collaborations. Collaboration in environmental matters is very important because environmental problems are complex problems, involve many parties, and have a broad impact, especially on the future of future generations. This research aims to describe the collaborative culture at the Rembang Regency Environmental Service and to explain the supporting and inhibiting factors in the implementation of collaborative culture at the Rembang Regency Environmental Service. The method used in this research is qualitative with interviews as the instrument. The results of the research show that the collaborative culture that has occurred so far has been running well, which is characterized by the existence of a work team, trust and positive empowerment carried out by employees of the Rembang Regency Environmental Service. However, miscommunication at the Waste Management UPT ultimately made the collaborative culture weak. Supporting factors consist of division of power, leadership, management style, and formalization, while inhibiting factors consist of unclear problem boundaries, unclear legal basis for collaboration, and low level of employee education. The suggestions given are to provide outreach regarding ASN work culture, organize further training and education for employees with low levels of education, collaborate with local stakeholders, and develop work guidelines that are clear and easy to understan